Effects of Grass Inter-Planting on Soil Nutrients, Enzyme Activity, and Bacterial Community Diversity in an Apple Orchard - Li, Tengfei; Wang, Yingying; Kamran, Muhammad; Chen, Xinyi; Tan, Hua; Long, Mingxiu (Frontiers in Plant Science, 2022)
Orchard inter-planting pattern has been widely used abroad, but it is still in its infancy in China. This study taking clean tillage orchard as control （CK），Soil nutrient, enzyme activity and bacterial community diversity in 0-10 cm, 10-20 cm and 20-40 cm soil layers were studied based on inter-row planting Lolium perenne （Lp） and Medicago sativa （Ms） in orchards.. Compared with CK, Lp and Lp+Ms significantly increased the contents of soil organic matter (OM), total nitrogen (TN), alkali-hydrolyzable nitrogen (AN) in 0-20 cm soil layer, and the activities of urease (URE) and alkaline phosphatase (ALP) (P < 0.05). The Lp treatment significantly (P < 0.05) increased the relative abundance of Gemmatimonadetes and Planctomycetes in the 0–10 cm soil layer. Besides, cover crops significantly increased the abundance of Actinobacteria, Gemmatimonadetes, and Chloroflexi in the 10–20 cm soil layer (P < 0.05) and that of Gemmatimonadetes and Chloroflexi (P < 0.05) in the 20–40 cm soil layer. Redundancy analysis (RDA) showed that Actinobacteria was positively correlated with ALP, OM and TN; Bacteroidetes was positively correlated with Available potassium (AK); Proteobacteria was positively correlated with available phosphorus (AP). In summary, grass interp-lanting improves the soil nutrients, enzyme activity, and bacterial community composition of the soil. According to this study, perennial ryegrass is the grass suitable for inter-planting in the apple orchards of Weibei, Shaanxi Province.